2016
DOI: 10.14689/ejer.2016.64.18
|View full text |Cite
|
Sign up to set email alerts
|

Social Studies Teachers’ Perceptions and Experiences of Social Justice

Abstract: Problem Statement: Social justice addresses inequality in society, including economic inequality, global migration, racism, xenophobia, prejudice against disabled people, and class discrimination. In Turkey, social studies curriculum aims to cultivate active, democratically minded citizens who value justice, independence, peace, solidarity, tolerance, freedom, and respect and demonstrate critical thinking skills, problem solving skills, social participation, and empathy.Purpose: Since social justice education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As a result of the research, pre-service teachers defined justice as being fair and discriminating between right and wrong. Bursa and Ersoy (2016) found that social studies teachers perceived social justice as a form of equality, justice, respect, tolerance and human rights in their studies of the perception and experience of social justice. According to the pre-service teachers, teachers' behaviors and teaching-learning process are important in gaining the value of justice.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the research, pre-service teachers defined justice as being fair and discriminating between right and wrong. Bursa and Ersoy (2016) found that social studies teachers perceived social justice as a form of equality, justice, respect, tolerance and human rights in their studies of the perception and experience of social justice. According to the pre-service teachers, teachers' behaviors and teaching-learning process are important in gaining the value of justice.…”
Section: Discussionmentioning
confidence: 99%
“…Especially for social studies subject, there are still many teachers who teach by giving memorizing material, instead of understanding material [2]. Even more, teachers present learning material without being followed by discussion or reflection with their pupils [3]. As a result, learning material obtained from schools is not used by pupils in interacting with their environment.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that there are some attempts to develop suggestions and programs for the ethical training of science teachers abroad [6][7][8][9]. In addition, there is some research focusing on the strategies to be followed in teaching of the ethical dimensions of socio-scientific issues within science courses [10][11][12], a reflection of technology on values and its teaching [13], determination of the role of classroom teachers on values education [14], qualifications to be possessed by ideal educators [15], the effect of content competences of science teachers on the quality of their socio-scientific argumentations [16] and the reflection of teachers' religious beliefs on ethics education [17].…”
Section: Introductionmentioning
confidence: 99%